Pengaruh Gaya Kepemimpinan Dan Etos Kerja Terhadap Kinerja Pegawai Dinas Kependudukan Dan Catatan Sipil Kabupaten Sleman - Indra Praja, Aris Suparman W (Universitas Muhammadiyah Yogyakarta, 2015)
This study is an empirically research the impact of leadership style and work ethic on employee performance employe of Civil Public and Population Registration Sleman Regency. the result of the research shown that the style of leadership and work ethic together provide a positive and significant effect, as shown by the magnitude of the coefficient of determination 0857 or 85.7% and the remaining 14.3% is influenced by other variables outside the model. Up and down, or the size of employee performance can be predicted by the regression equation Y = -11 258 + 0.137 X1 + 0.115 X2 X3 + 0177 + 0023 + 0940 X5 X4. Based on research that has been done can be deduced leadership style has no effect on performance while the work ethic significant effect on the performance of office workers of Civil Public and Population Registration Sleman Regency.Keywords : leadership style, work ethic, performance.